Pengaruh Pemberian Pill Card terhadap Kepatuhan Minum Obat Antihipertensi pada Pasien Hipertensi Rawat Jalan Puskesmas Rawat Inap Satelit Bandar Lampung - Audry Lintang Hasanuddin; Rasmi Zakiah Oktarlina; Dwi Aulia Ramdini; Oktafany Oktafany (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
Hypertension is one of the most common non-communicable diseases in Indonesia. Hypertensive patients must have high self-efficacy to comply with antihypertensive medication so that blood pressure can be controlled and complications prevented. Therefore, intervention is needed to improve therapy compliance. One intervention that can be given is the provision of pill cards. This study was a quasi-experimental design with a pre-intervention post-intervention control group design. Sampling was conducted using non-probability purposive sampling from July to September 2025. A total of 106 respondents were divided into two groups, with 53 respondents in the control group and 53 respondents in the intervention group. The control group was only given the MMAS-8 questionnaire, while the intervention group was given pill cards and the MMAS-8 questionnaire. In the intervention group, prior to intervention, 25 patients (47.2%) had low compliance, 21 patients (39.6%) had moderate compliance, and 7 patients (13.2%) had high compliance. After the intervention, there was a significant increase, with 21 patients (39.6%) showing high compliance, 26 patients (49.1%) showing moderate compliance, and 6 patients (11.3%) showing low compliance. Providing pill cards to outpatients with hypertension can improve patient medication adherence. Based on the results of the Wilcoxon Signed Ranks Test, a value of (p<0.001) was obtained, indicating that H0 was rejected and there was a significant effect.